A note on optimizing practical product warranty via linear pricing. Issue 2 (3rd March 2020) - Chien, Yu-Hung; Zhang, Zhe George; Wang, Jinting; Sheu, Shey-Huei
ABSTRACT: This note focuses on the problem of determining the optimal price and coverage period for warranted products from the manufacturer's perspective. The goal is to maximize the total profit for a planning period for the case where the demand for the product depends on the warranty coverage period and selling price. Since warranty period and selling price are positively correlated in a complex way under the optimality condition, we propose a simple rule of 'linearly pricing warranty period' to help practitioners to price the product with warranty to maximize the total profit. The assumption that the selling price is a linear function of the warranty period (warranty-based linear pricing) has been made in the literature. However, its effect on the manufacturer's profit has never been thoroughly investigated. We find that under some reasonable condition, this warranty-based linear pricing rule not only provides an easy way to price the product under a warranty with an appropriate coverage period in practice but also generates almost the maximum profit and capture more market share for the manufacturer. In addition, some managerial insights have been gained for practitioners in designing more competitive warranty and price policy.